Mutated Rnf43 aggravates Helicobacter pylori-induced gastric pathology - Neumeyer, Victoria; Vieth, Michael; Gerhard, Markus; Mejías-Luque, Raquel (Cancers, 2019)
Abstract: The E3 ubiquitin ligase ring finger protein 43 (RNF43) is frequently mutated in gastric tumors and loss of RNF43 expression was suggested to be one of the key events during the transition from adenoma to gastric carcinoma. Functional studies on RNF43 have shown that it acts as a tumor suppressor by negatively regulating Wnt signaling. Interestingly, we observed that RNF43H292R/H295R mice bearing two point mutations in the ring domain displayed thickening of the mucosa at early age but did not develop neoplasia. In this study, we infected these mice for 6 months with Helicobacter pylori, which has been described as one of the major risk factors for gastric cancer. Mice bearing mutant RNF43H292R/H295R showed higher gastritis scores upon H. pylori infection compared to wild-type mice, accompanied by increased lymphocyte infiltration and Ifng levels. Furthermore, infected Rnf43 mutant mice developed atrophy, hyperplasia and MUC2 expressing metaplasia and displayed higher levels of the gastric stem cell marker CD44 and canonical NF-κB signaling. In summary, our results show that transactivating mutations in the tumor suppressor Rnf43 can worsen H. pylori induced pathology.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Gastric pathology; H. pylori; RNF43